2022
DOI: 10.1111/1753-6405.13168
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory virus detection during the COVID‐19 pandemic in Queensland, Australia

Abstract: Objective : To determine if non‐pharmaceutical interventions (NPIs) impacted on respiratory virus detections in Queensland, Australia, during the COVID‐19 pandemic year of 2020. Methods : We analysed weekly counts of influenza, human metapneumovirus, parainfluenza, respiratory syncytial virus, rhinovirus, and adenovirus available from a Queensland laboratory network for the year 2020. These were compared with averaged counts from 2015 to 2019. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
4
32
1
Order By: Relevance
“…This caused a disease burden of pre-school children that possibly surpassed the burden of SARS-CoV-2 infections in this age group during the COVID-19 pandemic. The out of season increase of RSV detection is in line with studies from a number of countries covering five continents ( 9 14 ). Several studies also reported rates of infection by RSV that surpassed historical infection rates after public health measures had been reduced ( 15 17 ).…”
Section: Discussionsupporting
confidence: 86%
“…This caused a disease burden of pre-school children that possibly surpassed the burden of SARS-CoV-2 infections in this age group during the COVID-19 pandemic. The out of season increase of RSV detection is in line with studies from a number of countries covering five continents ( 9 14 ). Several studies also reported rates of infection by RSV that surpassed historical infection rates after public health measures had been reduced ( 15 17 ).…”
Section: Discussionsupporting
confidence: 86%
“…The study concluded that the PHSMs substantially decreased the seasonal influenza cases and activity [ 30 ]. The PHSM-implemented period was associated with a sharp and sustained decline in influenza-detection rates, from a zero detection rate out of 163,296 tests during weeks 23–40 of 2020 to 26.1% case-detection rate in the same period in 2015–2019 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…An 85% reduction in hospitalizations due to the parainfluenza (PIV) virus cases in children in 2020 was recorded in Hong Kong after the implementation of COVID-19 interventions as compared to previous years [ 32 ]. In 2020, during the PHSMs implementation period, a study reported that there were no cases of parainfluenza detected in the 70,618 tests performed compared with the 4.2% (1495/35,754) average detection rate in the 2015–2019 seasons [ 31 ]. In addition, children were likely more affected with the monthly incidence among children aged 0–4 years (120 per 100,000 children) being six times higher than the monthly incidence (21 per 100,000 children) during the previous 10 years [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second, the incidence of exacerbations is substantially lower than that predicted, a phenomenon found worldwide coincident with the public health measures enacted to reduce transmission of SARS-CoV-2. 54 Third, the reluctance of parents/patients to attend clinics during the pandemic prevented effective recruitment in some centres. Fourth, there are also financial consequences as no additional funds were made available by the funding body and research team members continued to be paid throughout this pandemic.…”
Section: Discussionmentioning
confidence: 99%